Promise that you will sing about me the power and poetry of Kendrick Lamar - Lewis, Miles Marshall 1970- (St. Martin's Press, 2021)
"From pop culture critic and music journalist Miles Marshall Lewis comes a book about the power and poetry of Kendrick Lamar! Kendrick Lamar is one of the most influential rappers, songwriters and record producers of his generation. Widely known for his incredible lyrics and powerful music, he is regarded as one of the greatest rappers of all time. Promise That You Will Sing About Me explores Kendrick Lamar's life, his roots, his music, his lyrics, and how he has shaped the musical landscape of this generation. With incredible graphic design, quotes, lyrics and commentary from Ta-Nehisi Coates, Alicia Garza and more, this book provides an in-depth look at how Kendrick came to be who he is today, his world, how he creates his lyrics and music, and how he revolutionizes the music industry from the inside"--